1991
DOI: 10.1016/0735-1097(91)90513-9
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic correlates of exercise function in patients with primary pulmonary hypertension

Abstract: The purpose of this investigation was to study the hemodynamic correlates of exercise function in patients with primary pulmonary hypertension and to further define the role of exercise testing in the evaluation of these individuals. Data from the progressive exercise tests and subsequent cardiac catheterization in 16 consecutive patients, aged 16.9 +/- 10.4 years (range 6 to 35), with primary pulmonary hypertension were prospectively collected and analyzed. Exercise capacity averaged 40 +/- 36% (range 0 to 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 19 publications
2
41
0
3
Order By: Relevance
“…Previous studies have shown that advanced PAH and CHF are both characterised by decreased peak work-rate, peak V9O 2 , V9O 2 at the anaerobic threshold and peak oxygen pulse, and increased ventilatory equivalents [2][3][4][5][6][7][9][10][11][12][13]. In the present patients, the anaerobic threshold occurred at a higher percentage of peak V9O 2 than in normal subjects.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…Previous studies have shown that advanced PAH and CHF are both characterised by decreased peak work-rate, peak V9O 2 , V9O 2 at the anaerobic threshold and peak oxygen pulse, and increased ventilatory equivalents [2][3][4][5][6][7][9][10][11][12][13]. In the present patients, the anaerobic threshold occurred at a higher percentage of peak V9O 2 than in normal subjects.…”
Section: Discussionsupporting
confidence: 43%
“…Increased ventilatory equivalents at exercise in CHF have been explained by a combination of increased dead space related to low cardiac output, early lactic acidosis [9] and increased chemosensitivity in the context of increased sympathetic nervous system tone [26]. Additional factors in PAH could include a greater increase in physiological dead space because of pulmonary vascular obliteration, and hypoxaemia on right-to-left shunting through a patent foramen ovale [2][3][4][5]27]. The present PAH patients exhibited a slightly lower Sp,O 2 at rest, and presented with exercise-induced hypoxaemia, which probably contributed to increase ventilatory equivalents and dyspnoea score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPET has been proven superior to other noninvasive testing to identify patients at high risk for heart catheterization (Rhodes, Barst, Garofano, Thoele, & Gersony, 1991). Poor exercise capacity (as a percent predicted of VO₂ max) in patients with primary PH put them at risk for RHC.…”
Section: Cardio Pulmonary Exercise Testmentioning
confidence: 99%
“…In the future it is suggested that these compromised patients are trained under professional supervision (Grunig et al, 2011;Grunig, et al, 2012). Training would help patients with IPAH increase VO₂ and 6MWD which would translate into increase of quality of life and life expectancy (H. Groepenhoff, et al, 2008;Miyamoto, et al, 2000;Rhodes, et al, 1991;Wensel, et al, 2002). Increasing pVO₂ by training would translate into using less percentage of pVO₂ during a 6MWT.…”
Section: Studymentioning
confidence: 99%